Рельеф и современные рельефообразующие процессы вулкана головнина и окружающих территорий (заповедник "курильский") - Grishchenko, Mikhail Yurievich; Shishkin, Vasiliy Sergeyevich (Київський національний університет імені Тараса Шевченка, 2017)
Цель. Вулкан Головнина является одним из самых активно посещаемых туристами объектов заповедника "Курильский" и острова Кунашир. Несмотря на это, он остаётся сравнительно слабо изученным в геоморфологическом отношении. Методика. Для восполнения этого пробела летом 2017 года здесь проведены детальные геолого-геоморфологические полевые обследования, в ходе которых составлено 180 геоморфологических описаний и заложено 25 геологических разрезов, проведено полевое и камеральное дешифрирование космических снимков сверхвысокого пространственного разрешения. Результаты. В результате проведённых исследований получены интересные выводы об эволюции сольфатарных полей, отмечены предполагаемые места давно потухших сольфатарных полей. Выявлены участки, наиболее сильно подверженные склоновым процессам. Описаны террасы озера Горячее и долины водотоков, впадающих в Охотское море. Научная новизна. Ранее такие исследования на рассматриваемой территории не проводились. Практическая значимость. Полученные результаты могут быть использованы в работе отдела экологического просвещения заповедника "Курильский", в том числе для планирования новых эколого-туристических маршрутов, к примеру, в живописные, богатые небольшими водопадами долины водотоков охотоморского побережья.

Purpose. Golovnin Volcano is one of the most actively visited objects of the nature reserve "Kurilsky" and the whole Kunashir island. Despite this, it remains relatively poorly studied in geomorphological terms. Methods. To fill this gap, in the summer of 2017, detailed geological and geomorphological field surveys were conducted here, during which 180geomorphological descriptions were compiled and 25 geological sections were laid, field and cameral interpretation of satellite images of ultra-high spatial resolution was carried out. Results. As a result of the conducted studies, interesting conclusions were obtained on the evolution of solfataric fields, the alleged sites of long-extinct solfatar fields were noted. The areas most vulnerable to slope processes are identified. The terraces of lake Goryachee and the valleys of watercourses flowing into the sea of Okhotsk are described. Scientific novelty. Previously, such studies were not conducted on this territory. The practical significance. The obtained results can be used by the environmental education department of the "Kurilsky" nature reserve, including planning new ecological and tourist routes, for example, to the picturesque valleys of the waterways of the Okhotsk Sea coast, rich in small waterfalls.
The Terrain and the Modern Geomorphological Processes of the Golovnin Volcano and Its Surroundings (State Nature Reserve "Kurilskiy")
Keywords: геоморфология; современные рельефообразующие процессы; вулкан Головнина; остров Кунашир; geomorphology; modern geomorphological processes; Golovnin volcano; Kunashir island